(untitled) (The Spectrum, 2026)
This study examines selected, representative episodes of Herne Katha, a YouTube-based documentary series produced in Nepal in which the directors and presenters—Bidhya Chapagain and Kamal Kumar— disseminate the multimodal digital stories of ordinary Nepali people. I argue this as an example of accessible multimodal and digital story has afforded to amplify the voices of the marginalized communities thus the Herne Katha team has contributed to social justice by bring the stories to public perceptions. The study has two purposes: to examine rhetorical elements and multimodal strategies mobilized in the selected episodes from the series, and to examine how the episodes bring forth the narratives and articulate critical concerns surrounding pervasive social issues in Nepal. To this ends, thematic textual analysis and rhetorical analysis was conducted by deploying the key concepts pertaining to multimodality and digital storytelling. The discussion shows the affordances of multimodal components of digital stories to bring forth the most entrenched issues of social justice of Nepal, such as caste-based discrimination, gender abuse, alcoholism, superstition, political frustration, unemployment, and poverty. The study concludes that the effective use of multimodal digital components facilitates viewers’ critical engagement with crucial social issues.